Study of atrazine adsorption kinetics by using an activated carbon synthesised from water hyacinth - Pawinee Deetae; Patthranit Wongpromrat (My University, 2019)
In this work, atrazine, one of the most widely used herbicides in Thailand, was removed from water by activated carbon synthesized from water hyacinth. Before adsorption, 3 types of activated carbons used as adsorbents were prepared by different chemical treatment methods; untreated activated carbon (AC), HCl-treated activated carbon (HCl-AC) and NaOH-treated activated carbon (NaOH-AC). After pyrolysis, NaOH-AC became ash, so it was not suitable for using as an adsorbent. Brunauer-Emmett-Teller (BET) and CHNS methods were used to characterised 2 other adsorbents and the results showed that HCl treatment could improve the surface area and carbon content. This led to the better performance of HCl-AC for removing atrazine from water comparing to AC confirming by the adsorption experiments. In addition, the adsorption kinetics of HCl-AC, the best adsorbent in this research, was investigated by fitting with 4 kinetics models. The results showed that pseudo-second-order was the best kinetics model describing that the atrazine adsorption of HCl-AC was limited by adsorption and 2 active sites of adsorbent were required for adsorbing 1 molecule of atrazine.
Keywords: Hyacinth; Carbon fibers; Adsorption and biosorption for pollutant removal